The Socio-cultural and Economic Dimensions of the Phenomenon of Illegal Immigration-Sociological Analyses in the Light of the Theory of Dominance - Nadjoua Amireche , Nadjoua Felkaoui (Migration Letters, 2024)
The phenomenon of illegal immigration is one of the aspects of human interaction in the North African coast, which necessitates a deep analytical study to reveal the reality of this phenomenon, especially in light of the increasing and growing influx of migrants from the countries of the South of Africa towards the countries of the North with the aim of migrating to the other side of the Mediterranean. This has made these countries a semi-permanent gateway of activity and movement for caravans of illegal immigration of various kinds. Therefore, the main challenge facing the issue of illegal immigration is fundamentally linked to the problems suffered by the countries of origin or the surrounding area, from disturbances and the weakness of their economic systems and the miserable social condition therein and the identity relational crisis that its inhabitants flounder in, contrary to the prevailing belief in the destination or central countries which promote the idea that this phenomenon cannot be controlled unless the problems faced by the surrounding countries are addressed through the establishment of peace, ensuring human rights, applying democracy, and achieving sustainable development. However, the reality is otherwise; it requires reconsideration of the relationship between the surrounding and central countries, which is dominated by manifestations of economic dependency and cultural dominance and what it has generated of problems, the most important of which is illegal immigration. This necessitates the intensification of efforts and delving into the underlying and implied causes that led to the proliferation of this phenomenon.